RANKING ONLINE SHOPPING APPLICATION USING FUZZY TOPSIS APPROACH - Muhamad, Siti Nor Nadrah; Pazil, Nur Syuhada Muhammat (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2026)
Nowadays, there are many online shopping applications used by modern society. However, the growth of online shopping applications has left users with a challenge of discerning the most reliable platform that meets with personal preferences. The wide range of alternatives complicates the decision-making process, requiring the need to determine the best alternative. Therefore, this paper aims to identify the best online shopping applications among students at UiTM Perlis by using Fuzzy Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) approach. During the analysis, primary data is collected through an online questionnaire distributed to UiTM Perlis students. In this study, it considers ZALORA, Shopee, TikTok Shop, SHEIN, and Lazada as alternatives. The criteria for evaluation are system quality, information quality, and service quality. The result of fuzzy TOPSIS highlights that Shopee as the top-ranked online shopping application, thus directly being acknowledged as the best among the alternatives. TikTok Shop comes in second, followed by ZALORA, Lazada and SHEIN. This study gives significant knowledge into the preferences of UiTM Perlis students, offering a practical application of the Fuzzy TOPSIS approach of making decisions in the realm of online shopping application and hence, contributes to the ongoing discussion over dependable approach for selecting the best online shopping apps particularly in the context of user satisfaction.